2022
DOI: 10.1038/s41432-022-0257-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and effectiveness of teledentistry: a systematic review of systematic reviews

Abstract: IntroductionThe COVID-19 pandemic has urged healthcare systems to develop new ways to safely provide care. Telehealth has become a compelling alternative. Our purpose was to evaluate the accuracy and effectiveness of teledentistry for screening, diagnosis and therapeutic management of dental care in children and adults. MethodsWe conducted a systematic review (SR) of systematic reviews. Multiple databases, the grey literature and conference archives were searched. Eligible SRs included those reporting virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…The asynchronous teleconsulting sessions have reportedly been one of the most offered and used [ 25 , 26 ], despite the low rates of utilization of teledentistry services [ 15 , 16 ] within the modalities offered by the telehealth program to support professionals. In this study, most of the teleconsulting sessions requested in 2020 avoided referring patients to other care levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The asynchronous teleconsulting sessions have reportedly been one of the most offered and used [ 25 , 26 ], despite the low rates of utilization of teledentistry services [ 15 , 16 ] within the modalities offered by the telehealth program to support professionals. In this study, most of the teleconsulting sessions requested in 2020 avoided referring patients to other care levels.…”
Section: Discussionmentioning
confidence: 99%
“…It reinforces the potential of dental teleconsulting in contributing to PHC effectiveness [ 1 , 4 , 14 , 15 , 16 , 27 ]. Teleconsultants clarify PHC professionals’ concerns and confirm patients’ diagnoses, qualifying them for the referral process [ 13 , 26 ], saving resources, time, and stress [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…found that teledentistry could be used as an acceptable tool to detect dental caries among children. With the rapid advancement of technology, such as high‐speed internet and the widespread use of mobile phones, the implementation of telehealth and teledentistry is becoming more feasible in clinical practice 8 …”
Section: Introductionmentioning
confidence: 99%